2022
DOI: 10.1002/tox.23465
|View full text |Cite
|
Sign up to set email alerts
|

The toxicity of cooking oil fumes on human bronchial epithelial cells through ROS‐mediated MAPK, NF‐κB signaling pathways and NLRP3 inflammasome

Abstract: Cooking oil fumes (COFs) are main pollutants in kitchen and indoor air, which threaten human health.Exposure to COFs can cause respiratory diseases and impair pulmonary function. To investigate the toxicity of COFs on human bronchial epithelial cells (Beas-2B) and explore the underlying mechanisms, MTT assay was conducted to detect the viability of Beas-2B. Intracellular reactive oxygen species (ROS) levels and nitric oxide (NO) levels were determined with DCFH-DA assay and DAF-FM assay. The expression of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Intracellular NO was detected using the fluorescent probe DAF-FM DA [ 26 ]. DAF-FM DA penetrates the cell membrane and is converted to DAF-FM by intracellular esterases, which cannot penetrate the cell membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular NO was detected using the fluorescent probe DAF-FM DA [ 26 ]. DAF-FM DA penetrates the cell membrane and is converted to DAF-FM by intracellular esterases, which cannot penetrate the cell membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have extensively documented the toxicological impact of COF on human cells. Nevertheless, there exists a paucity of literature concerning the real-time toxicity and metabolic effects of COF on human cells. In our current study, we found a significant correlation between the total number of identified substances and the number of identified unique substances in the COFs emitted during the heating of each oil.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the efficient ROS generation ability in solution, we used the 2ʹ,7ʹ-dichlorofuorescin diacetate (DCFH-DA) probe to test the intracellular ROS generation in different groups and analyzed by CLSM and Image J [ 40 ]. DCFH-DA has no fluorescence, but it can be rapidly converted into fluorescent 20, 70-dichlorofluorescein by ROS [ 41 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%